2010
DOI: 10.1371/journal.pbio.1000462
|View full text |Cite
|
Sign up to set email alerts
|

TRIM5 Suppresses Cross-Species Transmission of a Primate Immunodeficiency Virus and Selects for Emergence of Resistant Variants in the New Species

Abstract: Cross-species transmission of simian immunodeficiency virus from sooty mangabeys (SIVsm) into rhesus macaques, and subsequent emergence of pathogenic SIVmac, required adaptation to overcome restriction encoded by the macaque TRIM5 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
271
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(288 citation statements)
references
References 60 publications
(73 reference statements)
15
271
2
Order By: Relevance
“…82 It is also used to induce AIDS-like disease in rhesus macaques, although the degree of pathogenicity and viremia induced by this strain is highly variable. 75,82 Similar to the Lim study, this study also observed that SIVsmE543-3 replication in rhesus macaques is modulated by individual TRIM5a alleles. 75 By following the replication of virus in these animals over an extended period, the emergence of a TRIM5a-resistant strain of this virus in infected macaques that were originally able to control viral replication quite well was also noted.…”
Section: The Emerging Relationship Between Capsid Recognition Domainssupporting
confidence: 75%
See 3 more Smart Citations
“…82 It is also used to induce AIDS-like disease in rhesus macaques, although the degree of pathogenicity and viremia induced by this strain is highly variable. 75,82 Similar to the Lim study, this study also observed that SIVsmE543-3 replication in rhesus macaques is modulated by individual TRIM5a alleles. 75 By following the replication of virus in these animals over an extended period, the emergence of a TRIM5a-resistant strain of this virus in infected macaques that were originally able to control viral replication quite well was also noted.…”
Section: The Emerging Relationship Between Capsid Recognition Domainssupporting
confidence: 75%
“…75 By following the replication of virus in these animals over an extended period, the emergence of a TRIM5a-resistant strain of this virus in infected macaques that were originally able to control viral replication quite well was also noted. 75 Taken together, these two studies demonstrate that allelic diversity of the TRIM5a gene has the potential to differentially modulate the replication of viruses that individuals within a species may encounter.…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding when these adaptive changes occurred, together with how they altered the antiviral specificities of these genes, can lead to strong inferences about the existence of ancient viruses and their consequences on the modern function and specificity of the primate innate immune system. For example, although the TRIM5α protein encodes a retroviral restriction factor that blocks the viral life cycle of several retroviruses (3)(4)(5)(6)(7)(8), retroviral specificity varies among primates as a result of ancient selection for changes in antiviral specificity (9)(10)(11)(12). These species-specific differences in TRIM5α are due to dramatic variation in both the coiled-coil and B30.2 domains, which are responsible for the interaction with the viral capsid protein of a variety of retroviruses (13,14).…”
mentioning
confidence: 99%